Sistem Pendukung Keputusan Pemilihan Perumahan Menggunakan WASPAS - Huda, Azis Fatchul; Hadikurniawati, Wiwien (MEANS (Media Informasi Analisa dan Sistem), 2022)
Housing is one of the basic human needs and is an important factor in increasing human dignity. This is a very dominant problem in human survival to carry out all its activities. Prospective buyers are not easy in choosing housing, because hasty decision making will not provide the satisfaction expected by prospective buyers. In determining residential housing requires consideration to get a dwelling that fits your expectations, because everyone has different abilities. This study aims to create a decision support system for selecting the best housing in accordance with the wishes and needs using the WASPAS method with housing selection criteria including developer, price, land area, building area, distance to the city center. The recommendation from the selection criteria for the Bukit Semarang Jaya Metro developer using the WASPAS method is the Bukit Kencana Jaya housing estate with a Qi value = 0.872. Bukit Kencana Jaya has the highest value because it has a low price where the price criteria have the highest percentage weight. The combination of price advantage and weight advantage gives Bukit Kencana Jaya a high value.